Diagnostics in the veterinary field: The role in health surveillance and disease identification. (September 2019) - Holm, Anja; Hill, Richard; Farsang, Attila; Jungbäck, Carmen
Abstract: An international workshop, held in Wiesbaden, Germany on 15–17 May 2019 provided an overview of existing and new methods and approaches to diagnostics in animal health and their benefits and challenges. The variability in quality and authority review of test kits across the world is a concern for the reliability of test results and the decisions that are based on the diagnostic data. In countries or regions without regulatory oversight, there is an urgent need for international harmonisation of quality requirements and licensing procedures. This would increase the validity of the diagnostic methods and allow mutual recognition of test results within the network of official control laboratories and amongst animal health officials. Regional cooperation, as well as the OIE Laboratory Network, should be used to support licensing procedures, pool resources for serum and sample banks, survey outbreak responses, and coordinate research and development of new veterinary diagnostics. The end-users must have clear information on a test's performance, limitations, and interpretation of results. Highlights: Veterinary diagnostics show a concerning variability in quality and in authority review. International harmonisation of quality requirements and licensing procedures are urgently needed. Regional cooperation could support licensing, outbreak responses, and coordinate research. Clear information on a test's performance, limitations, and interpretation of results should be available for the end-users.